TGF-β-induced autophagy in pulmonary artery endothelial cells associated with chronic thromboembolic pulmonary hypertension - Ying-Ju Lai; Yen-Lin Huang; Ching-Yen Tsai; Po-Ru Chen; Chi-Jen Chang; Yung-Hsin Yeh; Celina De Almeida; Hsao-Hsun Hsu (Journal of Molecular Medicine, 2026)

Nonlinear structural reorganisation of corn starch induced by high-pressure processing regulates its thermal, pasting and hydration behaviour - Wen-Chien Lu; Yung-Jia Chan; Ching-Jung Lin; Zeng-Chin Liang; Po-Hsien Li (Food Chemistry, 2026)

Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Real-world emission factors and inhalation health risks of PM-bound metals from workboats using ultra-low sulfur marine fuel - Po-Yen Chien; Chia-Hsiang Lai; Chia C. Wang; Dhruv Vishal Patel; Ajay Pillarisetti; Wu-Xing Chen; Chia-Hung Chen; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Dong-Ni Wu; I-Hsuan Wu; et al. (Environmental Pollution, 2026)

Phylogeny and taxonomic revisions of Piper (Piperaceae) in Taiwan - Po-Hao Chen; Chia-Hao Chang; Kuan-Ning Kung; Hung‑Chih Lin; An-Ching Chung; Chia-Ying Ou; Shih-Hui Liu (Journal of Plant Research, 2026)
Taiwan, located at the northernmost extent of Huxley’s Line, marks the furthest point along this biogeographic boundary where exchanges of flora and fauna occur. The genus Piper , a globally distributed and taxonomically complex group of both economic and evolutionary importance, has a convoluted taxonomic history in this transitional zone that requires comprehensive study. Here, we integrate morphological, molecular, and distributional data to revise the taxonomy of Taiwanese Piper , resolve their evolutionary relationships, and infer their biogeographic history. Our revision recognizes 11 species in Taiwan, including seven native taxa, of which three are endemic. The present analysis establishes the first comprehensive phylogenetic framework for Taiwanese Piper and reveals that native species arose from lineages on both sides of Wallace’s Line. Collectively, these findings provide the first evidence of bidirectional expansion within a genus in Taiwan and position Piper as an exemplary system for examining phylogeographic dynamics in transitional biogeographic zones.

Biomass-inherent nitrogen doping in utilized chopsticks carbon for alkaline electrolysis - PratimaDevi Sivasubramanian; Yen-Ping Peng; Po-Hsun Lin; Subramanian Sakthinathan; Te-Wei Chiu; Ching-Lung Chen (Biomass and Bioenergy, 2026)

Plant–soil feedback persists beyond host death to shape density-dependent plant competition - Ching-Lin Huang; Joe Wan; Shuo Wei; Chia-Hao Chang-Yang; Po-Ju Ke (Plant and Soil, 2026)

Novel DUAL Z-SCHEME Bi2MoO6/SO3H@g-C3N4/ZnS photocatalyst enhanced by persulfate activation for rapid ofloxacin degradation: Integrated experimental and DFT studies - Imran Nasir Appau Zahir Hussain; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

Changes in Prooxidant and Antioxidant-Related Trace Element Levels During Helicobacter pylori Eradication Therapy - Ching-Chiang Lin; Ming-Kun Ku; Hsueh-Chiao Liu; Hui-Wen Chou; Po-Chih Chen; Deng-Chyang Wu; Yeou-Lih Huang (Biological Trace Element Research, 2025)

Mechanistic insights into capacitive ion exchange for selective divalent ion removal using activated carbon electrodes - Ming-Han Tsai; Shu-Ju Chao; David Chiuni Wang; I-Hsuan Lin; Li-Ching Chung; Po-I Liu; Lap-Cuong Hua; Hung-Yi Huang; Chi-Chang Hu (Chemical Engineering Journal, 2025)

Beyond tractography in brain connectivity mapping with dMRI morphometry and functional networks - Jui-To Wang; Ching-Po Lin; Huei-Min Liu; Carlo Pierpaoli; Chun-Yi Zac Lo (Brain Structure and Function, 2025)
Traditional brain connectivity studies have focused mainly on structural connectivity, often relying on tractography with diffusion MRI (dMRI) to reconstruct white matter pathways. In parallel, studies of functional connectivity have examined correlations in brain activity using fMRI. However, emerging methodologies are advancing our understanding of brain networks. Here we explore advanced connectivity approaches beyond conventional tractography, focusing on dMRI morphometry and the integration of structural and functional connectivity analysis. dMRI morphometry enables quantitative assessment of white matter pathway volumes through statistical comparison with normative populations, while functional connectivity reveals network organization that is not restricted to direct anatomical connections. More recently, approaches that combine diffusion tensor imaging (DTI) with functional correlation tensor (FCT) analysis have been introduced, and these complementary methods provide new perspectives into brain structure–function relationships. Together, such approaches have important implications for neurodevelopmental and neurological disorders as well as brain plasticity. The integration of these methods with artificial intelligence techniques have the potential to support both basic neuroscience research and clinical applications.

Understanding tractography in edematous brain regions: challenges and solutions - Shin Tai Chong; Joseph Yuan-Mou Yang; Ching-Po Lin (Brain Structure and Function, 2025)

Establishment of a pseudotargeted LC‒MS/MS workflow for analyzing triglycerides in biological samples - Wei-Chieh Wang; Chin-Yi Wang; Ta-Chen Su; Po-Chih Lin; Wen-Chi Chang; Kuei-Pin Chung; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Inhibition of testicular development by suppressing neonatal LH rise in male domestic pigs - ChanJin Park; Sandra Soto-Heras; Lindsey Reinacher; Katie Chai; Sherry Zhou; Po-Ching Lin; Ji-Eun Oh; Mary Bunnell; Rex A. Hess; Luiz Renato de França; CheMyong Ko (Animal Reproduction Science, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Multicenter study on clinical outcomes and poor prognostic factors in patients with Klebsiella pneumoniae bacteremia receiving cefoperazone/sulbactam treatment - Tsung-Ta Chiang; Ming-Hsien Chiang; Hung-Jen Tang; Zhi-Yuan Shi; Mao-Wang Ho; Chia-Hui Chou; Shang-Yi Lin; Po-Liang Lu; Ting-Shu Wu; Shian-Sen Shie; Jien-Wei Liu; Feng-Yee Chang; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Background Infections caused by Klebsiella pneumoniae are common and result in high mortality rates. In vitro studies demonstrated the potency of cefoperazone/sulbactam (CPZ/SUL) against Klebsiella pneumoniae . However, the clinical efficacy of CPZ/SUL for the treatment of K. pneumoniae bacteremia has not been studied. Objectives This study aimed to associate the clinical outcomes of patients with bacteremia with the minimal inhibitory concentrations (MICs) of CPZ/SUL against the causative K. pneumoniae isolates. Methods This multicenter, retrospective study was conducted in Taiwan between July 2017 and April 2021. Patients with K. pneumoniae bacteremia treated with CPZ/SUL were enrolled in this study. CPZ/SUL MICs were determined using the agar dilution method. Data on the patients’ clinical outcomes and characteristics were collected and analyzed. Results In total, 201 patients were enrolled. Among the causative K. pneumoniae isolates, 180 (89.5%) were susceptible to CPZ/SUL. Most patients ( n = 156, 77.6%) had favorable outcomes. The 30-day mortality rate was 11.9% ( n = 24). Multivariate risk analyses showed that higher APACHE II score (Odds Ratio [OR], 1.14; Confidence Interval [CI], 1.07–1.21; p < 0.001), metastatic tumors (OR, 5.76; CI, 2.31–14.40; p < 0.001), and causative K. pneumoniae CPZ/SUL MICs > 16 µg/ml (OR, 4.30; CI, 1.50–12.27; p = 0.006) were independently associated with unfavorable outcomes. Conclusion Patients with K. pneumoniae bacteremia treated with CPZ/SUL at a ratio 1:1 had favorable outcomes when the CPZ/SUL MICs were ≤ 16 µg/ml. Patients with higher APACHE II scores and metastatic tumors had unfavorable outcomes.

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Short-term Medication Effects on Brain Functional Activity and Network Architecture in First-Episode psychosis: a longitudinal fMRI study - Yajuan Zhang; Qiong Xiang; Chu-Chung Huang; Jiajia Zhao; Yuchen Liu; Ching-Po Lin; Dengtang Liu; Chun-Yi Zac Lo (Brain Imaging and Behavior, 2023)

An extended Human Connectome Project multimodal parcellation atlas of the human cortex and subcortical areas - Chu-Chung Huang; Edmund T. Rolls; Jianfeng Feng; Ching-Po Lin (Brain Structure and Function, 2022)

Spontaneous thought-related network connectivity predicts sertraline effect on major depressive disorder - Li-Ming Hsu; Timothy Joseph Lane; Changwei W. Wu; Chien-Yuan Lin; Chi-Bin Yeh; Hung-Wen Kao; Ching-Po Lin (Brain Imaging and Behavior, 2021)

Disinfection efficiency of hospital infectious disease wards with chlorine dioxide and hypochlorous acid - Ming-Chun Lu; Po-Lin Chen; Da-Ji Huang; Chih-Kuo Liang; Ching-Shan Hsu; Wei-Ting Liu (Aerobiologia, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Lactobacillus plantarum PS128 Ameliorated Visceral Hypersensitivity in Rats Through the Gut–Brain Axis - Yen-Wenn Liu; Yen-Po Wang; Hsu-Fang Yen; Pei-Yi Liu; Wen-Jian Tzeng; Chia-Fen Tsai; Han-Chieh Lin; Fa-Yauh Lee; One-Jang Jeng; Ching-Liang Lu; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Strictly Lobar Cerebral Microbleeds Are Associated with Increased White Matter Volume - Pei-Ning Wang; Kun-Hsien Chou; Li-Ning Peng; Li-Kuo Liu; Wei-Ju Lee; Liang-Kung Chen; Ching-Po Lin; Chih-Ping Chung (Translational Stroke Research, 2020)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

High Circulatory Phosphate Level Is Associated with Cerebral Small-Vessel Diseases - Chih-Ping Chung; Li-Ning Peng; Kun-Hsien Chou; Li-Kuo Liu; Wei-Ju Lee; Ching-Po Lin; Liang-Kung Chen; Pei-Ning Wang (Translational Stroke Research, 2019)

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Occurrence of Emerging Contaminants in Aquaculture Waters: Cross-Contamination between Aquaculture Systems and Surrounding Waters - Webber Wei-Po Lai; Yen-Ching Lin; Yu-Hsiang Wang; Yue Leon Guo; Angela Yu-Chen Lin (Water, Air, & Soil Pollution, 2018)

D-Cycloserine Ameliorates Autism-Like Deficits by Removing GluA2-Containing AMPA Receptors in a Valproic Acid-Induced Rat Model - Han-Fang Wu; Po See Chen; Ya-Ting Hsu; Chi-Wei Lee; Tzu-Feng Wang; Yi-Ju Chen; Hui-Ching Lin (Molecular Neurobiology, 2018)

Expression of serine peptidase inhibitor Kunitz type 1 in differentiated thyroid cancer - Chien-Liang Liu; Po-Sheng Yang; Ming-Nan Chien; Yuan-Ching Chang; Chi-Hsin Lin; Shih-Ping Cheng (Histochemistry and Cell Biology, 2018)

Mitochondrial and nuclear genetic structure in Rhodeus ocellatus (Teleostei: Cyprinidae) with approximate Bayesian computation - Jin-Quan Yang; Kui-Ching Hsu; Po-Hsun Kuo; Lin-Lin Li; Wen-Qiao Tang; Dong Liu; Hung-Du Lin (Environmental Biology of Fishes, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Impacts of hydrogeological characteristics on groundwater-level changes induced by earthquakes - Ching-Yi Liu; Yeeping Chia; Po-Yu Chuang; Yung-Chia Chiu; Tai-Lin Tseng (Hydrogeology Journal, 2018)

Alleviation of N-Methyl-d-Aspartate Receptor-Dependent Long-Term Depression via Regulation of the Glycogen Synthase Kinase-3β Pathway in the Amygdala of a Valproic Acid-Induced Animal Model of Autism - Han-Fang Wu; Po See Chen; Yi-Ju Chen; Chi-Wei Lee; I-Tuan Chen; Hui-Ching Lin (Molecular Neurobiology, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

Rapid Fabrication of a Cell-Seeded Collagen Gel-Based Tubular Construct that Withstands Arterial Pressure - Ho-Yi Tuan-Mu; Po-Ching Lu; Pei-Yuan Lee; Chien-Chih Lin; Chun-Jung Chen; Lynn L.H. Huang; Jia-Horng Lin; Jin-Jia Hu (Annals of Biomedical Engineering, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Time-Varying Network Measures in Resting and Task States Using Graph Theoretical Analysis - Chia-Yen Yang; Ching-Po Lin (Brain Topography, 2015)

Sulbactam treatment for pneumonia involving multidrug-resistant Acinetobacter calcoaceticus–Acinetobacter baumannii complex - Huang-Shen Lin; Ming-Hsun Lee; Chun-Wen Cheng; Po-Chang Hsu; Hsieh-Shong Leu; Ching-Tai Huang; Jung-Jr Ye (Infectious Diseases, 2015)

Rapid detection of copper chlorophyll in vegetable oils based on surface-enhanced Raman spectroscopy - Wei-Nan Lian; Jessie Shiue; Huai-Hsien Wang; Wei-Chen Hong; Po-Han Shih; Chao-Kai Hsu; Ching-Yi Huang; Cheng-Rong Hsing; Ching-Ming Wei; Juen-Kai Wang; Yuh-Lin Wang (Food Additives & Contaminants: Part A, 2015)

Occurrence of pharmaceuticals, hormones, and perfluorinated compounds in groundwater in Taiwan - Yen-Ching Lin; Webber Wei-Po Lai; Hsin-hsin Tung; Angela Yu-Chen Lin (Environmental Monitoring and Assessment, 2015)

The development of stream temperature model in a mountainous river of Taiwan - Ching-Pin Tung; Tsung-Yu Lee; Jr-Chuang Huang; Po-Wen Perng; Shih-Ji Kao; Lin-Yen Liao (Environmental Monitoring and Assessment, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

Mitochondrial DNA phylogeography of Semisulcospira libertina (Gastropoda: Cerithioidea: Pleuroceridae): implications the history of landform changes in Taiwan - Kui-Ching Hsu; Hor Bor; Hung-Du Lin; Po-Hsun Kuo; Mian-Shin Tan; Yuh-Wen Chiu (Molecular Biology Reports, 2014)

Effect of the BDNF Val66Met Polymorphism on Regional Gray Matter Volumes and Cognitive Function in the Chinese Population - Mu-En Liu; Chu-Chung Huang; Mu-Hong Chen; Albert C. Yang; Pei-Chi Tu; Heng-Liang Yeh; Chen-Jee Hong; Jin-Fan Chen; Jen-Ping Hwang; Ching-Po Lin; Shih-Jen Tsai (NeuroMolecular Medicine, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

Coherent activity between auditory and visual modalities during the induction of peacefulness - Chia-Yen Yang; Ching-Po Lin (Cognitive Neurodynamics, 2013)

Estimating Pumping Rates and Identifying Potential Recharge Zones for Groundwater Management in Multi-Aquifers System - Hsien-Tsung Lin; Kai-Yuan Ke; Yih-Chi Tan; Shih-Ching Wu; Gao Hsu; Po-Chia Chen; Shi-Ting Fang (Water Resources Management, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

Comparison of MODIS land surface temperature and ground-based observed air temperature in complex topography - Yen-Jen Lai; Ching-Feng Li; Po-Hsiung Lin; Tsong-Hue Wey; Cheng-Sheng Chang (International Journal of Remote Sensing, 2012)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Secular trend of genome types of respiratory adenovirus type 3 during 1983–2005: a study from Taiwan - Yung-Cheng Lin; Kuei-Hsiang Lin; Guan-Ming Ke; Min-Sheng Lee; Pei-Chin Lin; Hsin-Fu Liu; Li-Ching Hsu; Po-Liang Lu (Archives of Virology, 2010)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Vertical ozone distributions observed using tethered ozonesondes in a coastal industrial city, Kaohsiung, in southern Taiwan - Ching-Ho Lin; Chin-Hsing Lai; Yee-Lin Wu; Hsin-Chih Lai; Po-Hsiung Lin (Environmental Monitoring and Assessment, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

A Natural Compound (Ginsenoside Re) Isolated from Panax ginseng as a Novel Angiogenic Agent for Tissue Regeneration - Ya-Chun Huang; Chiung-Tong Chen; Sung-Ching Chen; Po-Hong Lai; Huang-Chien Liang; Yen Chang; Lin-Chien Yu; Hsing-Wen Sung (Pharmaceutical Research, 2005)